Secret honor - Burt, George (<<The>> Criterion Coll., 2004)
Portrays a disgraced President Richard Nixon recording memoirs in an attempt to defend himself and his political legacy.
Bildformat: 1.33:1 aspect ratio. - New high-definition digital transfer, with restored image and sound
Orig.: USA 1984
Enth. Audio commentaries with director Robert Altman and co-writer Donald Freed ; new 22-minute video interview with the actor Philip Baker Hall ; 81 minutes of archival-film excerpts from the political career of President Richard M. Nixon ; an essay by film critic Michael Wilmington
Keywords: Freed, Donald <1932-> - Adaptations cinématographiques et télévisées; Nixon, Richard M <1913-1994> - (Richard Milhous) - Films; Stone, Arnold M - Adaptations cinématographiques et télévisées; Nixon, Richard M. -- (Richard Milhous) -- 1913-1994 -- Drama.; Nixon, Richard M <1913-1994> -- (Richard Milhous) -- Drama; Nixon, Richard M. -- 1913-1994; Longs métrages - États-Unis; Feature films.; Präsident; USA; Film; DVD-Video; Biographical films; Feature films; Video recordings for the hearing impaired; Adaptation - Feature; Biographical - Feature; Political - Feature